Pelatihan Pengolahan Nugget Ikan untuk Meningkatkan Pendapatan Masyarakat di Pulau Lemon, Manokwari, Papua Barat: Fish Nugget Processing Training to raise community income in Lemon Island, Manokwari, West Papua - Dewi, Angela Myrra Puspita; Roreng, Mathelda Kurniaty; Tethool, Eduard Fransisco; Darma, Darma; Lisangan, Meike Meilan; Santoso, Budi; Faisol, Arif; Aman, Wilson Palelingan; Reniana, Reniana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Lemon Island is a small island in Manokwari Regency, West Papua. The livelihood of the people on Lemon Island is fishing for captured marine fish. Captured sea fish are prone to damage and spoilage during distribution, and the selling price is also low. Thus, it is necessary to educate the community about the need to process fishery products into fish nuggets to increase the shelf life of fish products and provide information to the community about the diversification of processed fish products. In addition, this community service activity is also expected to increase the income of coastal communities in Manokwari Regency, West Papua.